Mapping External Mortar Render (RAF) defects: case study in multi-storey residential buildings - Dias, Renan; PagotoLetícia; Tsutsumoto, Nayra; Fioriti, Cesar (Revista ALCONPAT, 2021)
This study aims to identify, map, and quantify the external mortar render (EMR) defects of 22 multi-storey buildings located in the Fernandópolis city, Brazil. Incidence (M-INC) and intensity (M-INT) methods were used to quantify the building defect (BD) of five typified facade regions: continuous wall (1-OCW), around openings (2-OOP), top of parapets and eaves (3-TOP), below balconies, soffits or ledges (4-BCE), and on corners and edges (5-OCE). In addition, three degradation pattern maps were created. We observed 4351 and 481 BDs by M-INT and M-INC, respectively. The most frequent problems were stains and cracks. The most affected regions by M-INT were 2-OOP (34.5%), 1-OCW (23.3%), and 4-BCP (21.6%) while by M-INC were 1-OCW (39.9%), 3- TOP (29.3%), and 2-OOP (16.6%).